The behavioral intention of micro enterprises to use the integrated cash waqf micro enterprise investment (ICWME-I) model as a source of financing - Mohd Thas Thaker, Mohamed Asmy; Mohammed, Mustafa Omar; Duasa, Jarita; Abdullah, Moha Asri (Universitas Gadjah Mada, 2016)
This study is designed to examine the behavioural intention of micro enterprises to use the Integrated Cash Waqf Micro Enterprise Investment (ICWME-I) model as a source of financing in Malaysia. The primary data are collected from the survey administered to micro entrepreneurs in the Klang Valley and the analysis is conducted using Structural Equation Modeling (SEM). Furthermore, the model has validated its acceptance in the field by adopting the Theory of Reasoned Action (TRA). This study has revealed that both the attitude and subjective norms are found to have a positive impact on the intention of micro entrepreneurs to use the ICWME-I Model in the context of Malaysia.